Determinasi Inovasi Produk Pada UMKM Sektor Makanan dan Minuman Halal di Kota Bekasi Utara - Neng Siti Komariah; Eri Bukhari; Ratna Suminar S; Adinda Sityowati; Nisrina Lathifah (Jurnal Ilmiah Ekonomi Islam, 2023)
This study analyzes the influence of technology orientation and customer orientation on the product innovation of Food and Baverage Halal MSMEs in North of Bekasi. This research uses quantitative methods and statistical analysis tools in the form of smartpls 4.0. This study used a Food and Baverage Halal MSMEs in North of Bekasi for a unit analysis. Sampling technique in this research with insidental sampling as 130 MSMEs. The results of this study found that there was an influence of techonolgy orientation and customer orientation on product innovation . This research focuses on the MSMEs in North of Bekasi. In addition, the focus of this research is on the Food and Baverage Halal. The novelty in this study is that apart from the object of research, it is also a research model that has never been studied before.